Analisis Bimbingan Orangtua dan Motivasi Belajar Siswa pada Pembelajaran Daring Selama Pandemi Covid-19 - Yulia Eka Yanti; Adzimatnur Muslihasari; Tety Nur Cholifah (Universitas Kanjuruhan Malang, 2021)
The corona virus has caused changes in the education system in Indonesia. This causes learning that was originally carried out face-to-face into learning from home. The Learning from Home system requires parents to play a full role in learning. To maintain and increase students' learning motivation while studying from home, parents really need the role. This research is a descriptive research with a qualitative approach. The instrument of data collection was done by interview and questionnaire. The subjects of this study were parents of grade II and III students at SD Negeri 2 Palaan located in Palaan Village, Ngajum District. The results of this study discuss the role of parents who are very influential in improving student learning outcomes of SD Negeri 2 Palaan during the Learning from Home System.